Tracking the international discourse of the Chinese super league through social media analytics. Issue 10 (27th September 2021) - Laurell, Christofer; Liu, Dongfeng; Soderman, Sten
Abstract: How is the international discourse of the Chinese Super League (CSL) framed in social media and which actors are driving current developments? Utilizing Social Media Analytics (SMA), we track the international discourse of the CSL and its associated actors throughout the social media landscape. Our findings reveal that the CSL is framed primarily by professional actors offering match information and results as well as betting and streaming services. Yet, fan engagement vis-à-vis CSL clubs, players and matches is limited in its extent. Thus, our results indicate that the international fan base of the CSL remains largely underdeveloped. Altogether, we contribute to extant literature in sports management by illustrating how an emerging methodological approach can be utilised, assessing a critical aspect of China's ambitions with regards to football, and the associated challenges that emerging leagues face in terms of attracting international fans despite considerable investment in recent years.